Billy the Kid : a short and violent life / Robert M. Utley. - Utley, R. M. (Tauris Parke, 2000)
Outlaw, hoodlum and killer, and slain at the age of 21 by Pat Garrett - Billy the Kid has become one of the icons of America's Wild West. This account tells the story of his brief and bloody life.